(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines the psychological burdens and supports experienced by Indian mothers caring for autistic children. Autism spectrum disorder (ASD) presents unique challenges that significantly impact caregivers, and this research focuses specifically on the experiences of mothers in India, a context where traditional gender roles and cultural expectations heavily influence caregiving dynamics. Through a mixedmethods approach combining qualitative interviews and quantitative surveys, this study explores the emotional, psychological, and social strains faced by these mothers. Key findings indicate that Indian mothers endure high levels of stress, anxiety, and depression due to the dual demands of managing their child’s autism and fulfilling societal expectations of motherhood and employment. The research highlights that caregiving responsibilities often lead to significant emotional isolation, financial strain, and a sense of personal inadequacy. Despite these challenges, the study also identifies various forms of support that can mitigate these burdens. Support systems include informal networks of family and friends, community-based organizations, and access to specialized services. However, gaps in institutional support and stigma associated with autism present barriers to effective caregiving and mental health maintenance. The study underscores the need for comprehensive support mechanisms, including improved mental health services, financial assistance, and enhanced public awareness of autism. By providing a nuanced understanding of the psychological impacts and support structures available to Indian mothers, this research aims to contribute to the development of targeted interventions and policies to better support this vulnerable population.